CUSHING’S DISEASE PRESENTING YEARS AFTER PITUITARY APOPLEXY: A CASE REPORT - Miao, Tan Jia; Chan, Lim Fang; Ching, Tee Hwee; Hatta, Siti Nabihah Mohamed (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Pituitary apoplexy is a life-threatening condition resulting from haemorrhage or necrosis of a pituitary tumour. After an apoplectic event, recurrence of pituitary adenoma from the remaining pituitary tissue is still possible. We report an interesting case who had cushingoid features that manifested several years after her initial episode of pituitary apoplexy. CASE A 29-year-old female initially presented with a sudden onset of headache and diplopia. Clinically, she had left cavernous sinus syndrome. A cranial MRI showed a normal-sized pituitary gland with an internal haemorrhage suggestive of apoplexy and no filling defect within the cavernous sinus. She had hypocortisolism post pituitary apoplexy and needed hydrocortisone replacement. Her subsequent yearly MRI surveillance showed a normal-sized pituitary gland with no residual haemorrhage. Three years later, she exhibited typical full-blown cushingoid features of the moon face, facial plethora, proximal myopathy, hirsutism and purplish striae over the abdomen. Hydrocortisone replacement was withheld as repeated morning cortisol was 1002 nmol/L (145.4- 619.4) raising the possibility of endogenous hypercortisolism. On further evaluation, she had an increased 24-hour urinefree cortisol, and abnormal serum cortisol during both overnight dexamethasone suppression test and low-dose dexamethasone suppression test. Laboratory findings strongly supported ACTH-dependent Cushing’s syndrome whereby plasma ACTH was elevated at 20.58 pmol/L (1.6- 13.9). However, her brain MRI did not show any evidence of a pituitary adenoma, hence underwent inferior petrosal sinus sampling to further evaluate the likely possibility of Cushing’s disease. CONCLUSION This case demonstrates the possibility of recurrence Cushing’s disease years after an episode of pituitary apoplexy, whereby the residual ACTH-producing adenoma might have grown slowly to form the second tumour. Therefore, long term monitoring is crucial for patients with pituitary apoplexy as they may develop tumour recurrence as well as hormonal deficiencies or excesses over time